TLC-bioautography directed isolation of antibacterial compounds from active fractionation of Ferula ferulioides. Issue 12 (18th June 2019) - Sun, Zhong-Lin; Liu, Tao; Wang, Shuang-Ying; Ji, Xiao-Yue; Mu, Qing
Abstract: A novel optimised isolation method, TLC-bioautography, was evaluated and utilised in this research. Antibacterial compounds which were isolated from the dichloromethane extract of Ferula ferulioides (Steud.) Korovin were detected by means of the method. Their structures were elucidated by extensive spectral and chemical methods. Their antibacterial activities against drug-resistant Staphylococcus aureus ( S. aureus) strains were evaluated with broth microdilution method, and the results proved that TLC-bioautography was an effective and highly efficient way to screen natural compounds from plant extracts against drug-resistant strains. Abstract :